KEKERASAN, KORUPSI DAN PEMILUKADA - Fitriyah, Fitriyah (FORUM, 2011)
Abstract :Corruption scandals surrounding  of  local budgeting is one of structural violence,  is paradox to increase the efficiency and responsiveness of the public sector. Local  head elections   increase in the number of regional heads who are involved in corrupt acts. There are 17 governors   and  138  regents and mayors across the country are currently under investigation or serving prison sentences related to corruption.  Why does corruption happen? The factor behind the rampant political corruption is regulation of  voting system led to expensive  political cost, not only in campaign funding but also in  candidate recruitment system.  In order to   minimize the potential for corruption and avoid the temptation of using of regional budgets  by recover election  laws, we must democratize party recruitment and we must limit campaign spending by regional head candidatesKey words:  violence, corruption, local electionspermalink:http://ejournal.undip.ac.id/index.php/forum/article/view/3152